PERLINDUNGAN HUKUM NASABAH PEMEGANG KARTU KREDIT TERHADAP ADANYA PERBUATAN MELAWAN HUKUM YANG DILAKUKAN OLEH DEBT COLLECTOR - Kurniawan, Amalia; Budi Arsika, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014)
This paper discusses the consumptive use of credit card that ultimately led to theinability of credit card holders to pay the debt, that makes banks have to use debtcollector service to collect the debt. It aims to identify the legal protection of credit cardcustomers from any actions taken by debt collectors and also to analyze theresponsibility of debt collectors for their actions. It is a normative legal research thatuses statutory and analitical-conseptual approaches. It can be concluded that the creditcard holders are given legal protection from the Regulation of Bank Indonesia (CentralBank). In case loss of credit card holders, both banks and debt collectors have differentresponsibility. More specifically, the bank is responsible to provide compensation in theform of a sum of money to the customer, meanwhile, debt collectors will be imposedcriminal responsibility for their actions.
Keywords: Credit card, Customer, Legal Protection, Debt Collector